Effective fluorination of single-layer graphene by high-energy ion irradiation through a LiF overlayer. Issue 72 (19th July 2016) - Entani, Shiro; Mizuguchi, Masaki; Watanabe, Hideo; Antipina, Liubov Yu.; Sorokin, Pavel B.; Avramov, Pavel V.; Naramoto, Hiroshi; Sakai, Seiji
Abstract : A new non-chemical method for heteroatom doping into single-layer graphene was demonstrated by high-energy ion irradiation of the graphene-based heterostructure. Abstract : A new non-chemical method for heteroatom doping into single-layer graphene was demonstrated by high-energy ion irradiation of the graphene-based heterostructure. The heterostructure was fabricated by depositing a LiF layer on a single-layer graphene sheet which was grown on a Cu substrate by chemical vapor deposition. We successfully obtained fluorinated graphene by 2.4 MeV 63 Cu 2+ ion irradiation through the LiF overlayer. Raman spectroscopy, near edge X-ray absorption fine structure spectroscopy and X-ray photoelectron spectroscopy revealed that 20%-fluorinated graphene is obtained superior to the defect formation by the high-energy ion irradiation up to 10 14 ions per cm 2 . It was also shown that the F atoms are chemically adsorbed on single-layer graphene by the C–F bonds in a similar manner to the fluorinated graphene synthesized by the purely chemical route. The mechanism of the fluorination by the ion irradiation is discussed in terms of electronic excitations of carbon and heteroatoms based on the spectroscopic results.